The Reflection of Register Used in Glow Up Season 4 - Sidqi, Farradifa Natasya (Language Horizon: Journal of Language Studies, 2023)
To become a makeup artist, knowledge about makeup registers is certainly one of the things that must be known. This study aims to classify the word formations from the register, identify the situational characteristics of the register, and analyze the reflection of the register in the identity of the makeup area mastered by the makeup artist in Glow Up Season 4. This study used a qualitative approach where the data are conversations between the makeup artists’ contestants and the judges which were collected by documentation technique. There are six steps to analyze the data, which are organizing and preparing, reading, coding, developing a coding scheme, identifying, and interpreting the data. The study found 122 data, of which the types are 30 affixations, 65 compounding, and 27 derivation without affixations. The actual time of each register in the form of before and after, while the actual place of the registers follows the challenges. The study also found that character makeup is mastered by Ratz and Meager, corrective makeup is mastered by Rose, and style makeup is mastered by Lily and Calendula from the reflection of register used. It can be concluded that the word formation that appears most often is compounding, most of these registers have an actual time which shows the step in makeup and appear in Glow Up Season 4 makeup studio as the actual place, and some registers only appeared in one makeup area reflect the identity of the makeup area mastered by the makeup artist.